2021
DOI: 10.1016/j.healthpol.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Corona-regionalism? Differences in regional responses to COVID-19 in Italy

Abstract: The paper discusses the responses to the COVID-19 crisis in the acute phase of the first wave of the pandemic (February-May 2020) by different Italian regions in Italy, which has a decentralised healthcare system. We consider five regions (Lombardy, Veneto, Emilia-Romagna, Umbria, Apulia) which are located in the north, centre and south of Italy. These five regions differ both in their healthcare systems and in the extent to which they were hit by the first wave of COVID-19 pandemic. We investigate their diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Firstly, our data are related to the experience in one region and not extendible to a national level. With regard to this issue, Bosa et al [ 39 ] reported that the Italian National Health System did not approach the pandemic as a united front, as differences were underlined from one region to another. In fact, misunderstandings and consequent tensions between central government and regions most likely lead some regions to take autonomous decisions (centrifugal drive), whereas others followed the government to avoid taking the burden of owning the responsibility (centripetal drive) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, our data are related to the experience in one region and not extendible to a national level. With regard to this issue, Bosa et al [ 39 ] reported that the Italian National Health System did not approach the pandemic as a united front, as differences were underlined from one region to another. In fact, misunderstandings and consequent tensions between central government and regions most likely lead some regions to take autonomous decisions (centrifugal drive), whereas others followed the government to avoid taking the burden of owning the responsibility (centripetal drive) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to this issue, Bosa et al [ 39 ] reported that the Italian National Health System did not approach the pandemic as a united front, as differences were underlined from one region to another. In fact, misunderstandings and consequent tensions between central government and regions most likely lead some regions to take autonomous decisions (centrifugal drive), whereas others followed the government to avoid taking the burden of owning the responsibility (centripetal drive) [ 39 ]. Secondly, the different specific issues were not investigated in depth in order to avoid an excessive length of the questionnaire; this could have hidden important information, e.g., those related to the use of telematic monitoring of glucose in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the coronavirus pandemic in Italy, the weekly incidence rates of infections differed significantly among Italian regions [ 47 ] and were highest and vaccination rates were lowest in South Tyrol, where German and Italian speakers live together [ 20 , 48 , 49 ]. Experts link vaccine hesitancy in the northernmost province of Italy to a cultural disposition and historic link to Austria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of the onset and development of the COVID-19 pandemic in Italy also reflect the Italian territorial differences, with most deaths concentrated in the north, the most industrialized and polluted area (Aloisi et al, 2022 ; Bosa et al, 2021 ). Moreover, the recent development of COVID-19 vaccinations, especially in Europe and the USA as the most advanced areas in the pharmaceutical sector (Aldieri et al, 2020 ), is also expected to increase anxiety levels in the near future (Bodner et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%